2022
DOI: 10.1192/bjp.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Autism and autistic traits in those who died by suicide in England

Abstract: Background Autism and autistic traits are risk factors for suicidal behaviour. Aims To explore the prevalence of autism (diagnosed and undiagnosed) in those who died by suicide, and identify risk factors for suicide in this group. Method Stage 1: 372 coroners’ inquest records, covering the period 1 January 2014 to 31 December 2017 from two regions of England, were analysed for evidence that the person who died had diagnosed autism or undiagnosed possible autism (elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 27 publications
2
34
1
1
Order By: Relevance
“…Those with ASD/DD had higher rates of externalizing features relative to peers, but lower rates of depression, anxiety, and suicidal ideation and attempts. This contrasts with outpatient data indicating heightened internalizing disorders in ASD (e.g., [ 4 ]), as well as with elevated rates of suicidal ideation and behavior among adults with ASD [ 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Those with ASD/DD had higher rates of externalizing features relative to peers, but lower rates of depression, anxiety, and suicidal ideation and attempts. This contrasts with outpatient data indicating heightened internalizing disorders in ASD (e.g., [ 4 ]), as well as with elevated rates of suicidal ideation and behavior among adults with ASD [ 29 , 30 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Sample size calculations were based on Pelton et al [ 9 ], who reported effect sizes ( f 2 ) of 0.11 (the upper end of small) and 0.18 (medium) in regression analyses for suicide ideation and attempts in autistic people. For the number of predictors in our own models of suicide ideation [ 5 ] and attempts [ 7 ], with power set at 90% and predicted effect size as small (in order to be conservative), minimum required sample sizes would have been 156 and 174 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Suicide ideation, attempts and deaths are unacceptably high in autistic adults without intellectual disabilities [ 1 5 ]. Factors associated with suicide ideation and attempts include loneliness and unmet support needs [ 6 , 7 ], self-injury [ 6 , 8 ], psychiatric illnesses and post-traumatic symptoms [ 4 , 9 ], rumination and low self-worth [ 10 ], and the extent to which individuals camouflage their autism [ 6 ].…”
mentioning
confidence: 99%
“…The current research exposes the very real cost of such policies to autistic, or otherwise neurodivergent, children and young people’s mental health. These findings must also be considered with respect to autistic individuals’ increased vulnerability to severe mental health difficulties, suicidality (110), attempted suicide (142), and death by suicide (111, 112), with rates of suicidal ideation and suicide attempts being significantly higher for autistic children (14%) than for their neurotypical peers (0·5%) (113). In addition to such research showing increased risk of suicide in autistic individuals broadly, Hirvikoski et al’s study using population-level data from Sweden (112) found that autistic people without a co-morbid intellectual disability are more likely to die by suicide (odds ratio = 9.40).…”
Section: Discussionmentioning
confidence: 99%
“…Such elevated scores are of concern, not least because higher anxiety severity is associated with a lower quality of life in both autistic and non-autistic children with anxiety disorders (108), and in autistic CYP more generally (107,109). Moreover, such scores need to be considered with respect to the high prevalence of suicidality and death by suicide documented in autistic individuals e.g., (110)(111)(112)(113) (see below for further discussion). Hence, supporting individual CYP who are experiencing such levels of anxiety, and their families, should be first and foremost in the minds of the educational and health-care professionals surrounding these CYP.…”
Section: Characteristic Of the Cyp With School Distressmentioning
confidence: 99%